Global biogeography - Briggs, John C. (Developments in palaeontology and stratigraphy ;, 1995)
This book significantly expands the coverage of this subject given by its predecessor Biogeography and Plate Tectonics (1987). Global Biogeography traces global changes in geography and biology from the Precambrian to the Recent (with worldwide coverage in chronological order); examines the evolutionary effects of the major extinctions, and discusses contemporary biogeographic regions within the context of their historic origins. It is now apparent that the biotas of the various biogeographical regions have had, and still maintain, a dynamic relationship with one another; much more than was previously thought. This is shown to be true for all three of the earth's primary habitats; marine, terrestrial and freshwater (as is clearly demonstrated in this volume). The book is splendidly illustrated with 122 text figures, an extensive bibliography, index, together with a set of biogeographic maps illustrating continental and terrain outlines from the mid-Cambrian to the Recent. University students (both advanced undergraduate and graduate level) will find it an excellent text book. For professionals in Biogeography this is a convenient reference work.